A Comparison Analysis of the Experimental and Theoretical Power Output of a Hybrid Photovoltaic Cell. (25th March 2019) - Paul, Damasen Ikwaba
Abstract : In this paper, experimental and theoretical power output of a hybrid photovoltaic cell were analysed and compared for three different weather conditions (clear sky, partial cloudy, and overcast days). The hybrid photovoltaic cell consisted of low efficiency cell (mono-crystalline) and strips of Bosch M 2BB mono-crystalline cell as high efficiency cell. The current and voltage for the experimental results were measured by using optimal resistive load method. Theoretical daily power output of the hybrid PV cell was calculated based on the hourly incident energy on each section, the size of the section, and the electrical conversion efficiency of each section. The hybrid cell was evaluated within a low-concentrating symmetric compound parabolic concentrator suitable for building integration and was tilted at 54°. It was found that the theoretical daily power output on a clear sky, partial cloudy, and overcast days was higher than the experimental results by 136%, 109%, and 121%, respectively. The discrepancy was due to losses as the result of connecting wires series resistance effect, operating temperature effect, and the consequence of the fixed resistive load. However, it was the value of the optimal resistive load that had much impact on the experimental power output. To eliminate the restriction of the optimal resistive load on the experimental results, it is recommended to use data acquisition systems such as photovoltaic peak power measuring device 6020C 6020C or Keithley 2651A source-meter.